Key Residues and Phosphate Release Routes in the Saccharomyces cerevisiae Pho84 Transceptor: THE ROLE OF TYR179 IN FUNCTIONAL REGULATION - Samyn, Dieter R; Van der Veken, Jeroen; Van Zeebroeck, Griet; Persson, Bengt L; Karlsson, Björn C G (The Journal of biological chemistry, 2016)
Pho84, a major facilitator superfamily (MFS) protein, is the main high-affinity P transceptor in Saccharomyces cerevisiae Although transport mechanisms have been suggested for other MFS members, the key residues and molecular events driving transport by P :H symporters are unclear. The current Pho84 transport model is based on the inward-facing occluded crystal structure of the Pho84 homologue PiPT in the fungus Piriformospora indica However, this model is limited by the lack of experimental data on the regulatory residues for each stage of the transport cycle. In this study, an open, inward-facing conformation of Pho84 was used to study the release of P A comparison of this conformation with the model for P release in PiPT revealed that Tyr in Pho84 (Tyr in PiPT) is not part of the P binding site. This difference may be due to a lack of detailed information on the P release step in PiPT. Molecular dynamics simulations of Pho84 in which a residue adjacent to Tyr , Asp , is protonated revealed a conformational change in Pho84 from an open, inward-facing state to an occluded state. Tyr then became part of the binding site as was observed in the PiPT crystal structure. The importance of Tyr in regulating P release was supported by site-directed mutagenesis and transport assays. Using trehalase activity measurements, we demonstrated that the release of P is a critical step for transceptor signaling. Our results add to previous studies on PiPT, creating a more complete picture of the proton-coupled P transport cycle of a transceptor.